Seismic architecture of a Miocene isolated carbonate platform and associated off-platform strata (Central Luconia Province, offshore Malaysia). (April 2019) - Rankey, Eugene C.; Schlaich, Markus; Mokhtar, Sofiyah; Ghon, George; Ali, Syed Haroon; Poppelreiter, Michael
Abstract: Rather than being homogeneous and isotropic, many isolated carbonate platforms in the geologic record include internal heterogeneity and complex geometric relations with off-platform strata on their flanks. To better understand stratal architecture of a Miocene isolated platform (Central Luconia, offshore Malaysia), this study integrates core, log and seismic data, revealing stratal terminations and geometries that define several seismic stratigraphic units. A thick in the basal seismic unit, the initial deposits of the carbonate buildup, is 4–5 km across. This thick includes abrupt thinning to the west and east, with onlap onto its flanks, but continues outside of the survey area to the north and south. Above a mappable surface, a less extensive (2 × 5 km) seismic unit represents a backstepped isolated platform (Platform Stage 1). Across a pronounced normal fault on the east/southeast margin of the platform occur marked isochron and seismic character changes, with thicker carbonates on the downthrown (western) block. The northern and western margins are not faulted. A third seismic unit, representing a smaller, elongate (<1 × 3 km), N-S trending carbonate platform (Platform Stage 2), reflects a second backstep. The top of this unit in core is associated with karst, suggesting subaerial exposure; the surface can be traced off the platform and across the fault, to an (upthrown) area with irregular amplitude and similarity, interpreted to represent karst. These strata – and several other reflectors that dim and decrease loop duration away from the buildup ("wings") - sit atop one of a series of north-prograding clinoforms (siliciclastic "wedges"). In turn, two chronostratigraphically distinct wedges that onlap and thin away from the thick of Platform Stage 2 are interpreted to be carbonate (platform stages 3 and 4), and are onlapped by another succession of off-platform clinoforms (interpreted as siliciclastic). All of these strata are capped by another elongate (<1 × 2 km) seismic unit (Platform Stage 5), before the platform is covered with siliciclastics. The most marked stratigraphic theme within the isolated platform is the successive backsteps, but the pattern is complicated by interactions with the basinal strata. Superposition and cross-cutting relations document that isolated platform-sourced flanking beds ("wings") interfinger with basinal clinoforms ("wedges"), as defined by geometries on the margins and flanks of platform stages. The platform evolution also was influenced markedly by syndepositional structural activity, although structural trends changed from the initial buildup to later platform stages. The results, and comparison with other isolated platforms, demonstrate the complex controls on carbonate platform growth and interactions with basinal siliciclastics. Graphical abstract: Image 1 Highlights: Seismic stratigraphy of isolated carbonate platform and basinal strata. Platform includes several stages of growth, separated by backsteps. Platform flanked by talus "wings" interfingered with basinal siliciclastic "wedges". Syndepositional structural deformation markedly influenced platform architecture.